Innovation Balance Matrix: an application in the Arab countries. (1st June 2006) - Abouzeedan, Adli; Busler, Michael
Economies have different levels of entrepreneurial activities depending on the availability of tangible as well as intangible resources. In their working paper, Abouzeedan and Busler (2004) established a new type of capital, adding up the components of the most important types of capital. These are the human capital, financial capital and the system capital. In that paper, the two researchers defined each of the components and explained what they meant with those terminologies. They called this new type of capital, innovation capital. The two researchers have argued that innovation capital can be used as an indicator for the degree of richness of the entrepreneurial environment in a region and thus the general character of the economy. They also introduced the Innovation Balance Matrix or IBAM as an analytical tool to classify economies based on their entrepreneurial conditions. In this extended work, they have used this analysis and tried to apply it to Arab countries using a general knowledge and deductive approach to the issue. They conclude the paper with some recommendations as how to enrich the innovation capital in that region.